Consumers' human nature and their shopping channel choices in the emerging artificial intelligence era: based on Xunzi's humanity hypothesis. Issue 4 (17th August 2020) - Deng, Guangkuan; Zhang, Jianyu; Ye, Naiyi; Chi, Rui
Abstract : Purpose: Drawing from the ancient Chinese philosopher Xunzi's insights on humanity, this study aims to address human nature's critical role in influencing and shaping consumers' shopping channel choices in the emerging artificial intelligence (AI) era and the implications for non-East Asian countries. Design/methodology/approach: Based on the theory of planned behaviour and accessibility–diagnosticity theory, our approach created a holistic model conceptualising human nature, shopping orientations, channel choice intentions, subjective norms and perceived AI usefulness. A questionnaire survey method served to test the framework. Findings: The results validated human nature's role in shaping and influencing consumers' channel choices through shopping orientation. Subjective norms weaken the positive relationship between human nature and shopping orientation, while the positive relationship between shopping orientation and online purchase intention is stronger when consumers perceived AI as highly useful. Originality/value: This paper contributes to humanity hypotheses literature in management by introducing Xunzi's theory that views human nature as evil. Additionally, it enriches channel choice literature by introducing perceived AI usefulness.